Careers in healthcare and beyond : tools, resources, and questions to prepare you for what's next - Lee, Evelyn (New York : Productivity Press, 2021)
According to the U.S. Bureau of Labor Statistics, some of the fastest projected job growth will occur in the healthcare, healthcare support and personal care fields which accounts for almost one third of the total employment growth by 2020. Analysts suggest that the healthcare field is growing because of the long-term trends of an aging population and improved diagnosing and treatment options. Additionally, technology advances in telemedicine and telehealth are allowing elderly patients to remain in their homes as they age even though their health needs are increasing. All these advances and changes to payment structures are fueling the employment growth opportunities in healthcare. This book is intended for someone curious to learn more about a career in healthcare, but not certain if it is right for them, or if the industry would be a good fit for them. For the person who is already interested in pursuing a career in healthcare, it provides added excitement to continue on this path. For the person who is less certain, it explores in a narrative format, the unique opportunities that are available in healthcare, and career options that are not obvious to the general public. It is designed to provide added insights and stories that will inspire one to learn more about the field of healthcare and the many opportunities to consider. It will encourage readers to explore ways to gain hands-on experience to determine what is the best approach for them to take to start this journey. This book is also intended for those who currently work in healthcare but may be considering a different job in the field.
OCLC-licensed vendor bibliographic record.
Keywords: Medical care -- Vocational guidance -- United States; BUSINESS & ECONOMICS / Quality Control; BUSINESS & ECONOMICS / Industries / Service Industries; BUSINESS & ECONOMICS / Production & Operations Management